2020
DOI: 10.3390/polym12061301
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Comparative Study of Nanoparticles Derived from Bovine and Human Serum Albumins

Abstract: This study describes the preparation of nanoparticles derived from bovine serum albumin (BSA) in comparison with the formation of nanoparticles composed of human serum albumin (HSA), when the same preparation procedure was used in both cases. To obtain protein nanoparticles, the method of desolvation with ethanol was employed, followed by the stabilization with urea and cysteine. It was shown that, upon transition from HSA to BSA, the particles with smaller sizes and with a narrower polydispersity were formed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…It is known that HSA and BSA share 80% sequence homology, their molecular weights differ by less than 1%, and their isoelectric points are identical. Nevertheless, the finding obtained in this study is in agreement with the work conducted by Tazhbayev et al (61), who demonstrated that the average particle size of BSA-derived nanoparticles (167 ± 5 nm) was smaller than that of HSA-derived nanoparticles (216 ± 9 nm).…”
Section: Discussionsupporting
confidence: 93%
“…It is known that HSA and BSA share 80% sequence homology, their molecular weights differ by less than 1%, and their isoelectric points are identical. Nevertheless, the finding obtained in this study is in agreement with the work conducted by Tazhbayev et al (61), who demonstrated that the average particle size of BSA-derived nanoparticles (167 ± 5 nm) was smaller than that of HSA-derived nanoparticles (216 ± 9 nm).…”
Section: Discussionsupporting
confidence: 93%
“…In this case, urea plays the role of a chaotropic agent, which unfolds albumin chains and increases the availability for interaction with cysteine. As a result, the thiol-disulfide exchange reaction between BSA NPs macro-chains is stabilized [12][13][14]. In addition, the authors of the present work [15] have shown that cysteine can play a positive role in overcoming MDR.…”
Section: Introductionmentioning
confidence: 60%
“…Albumin-based nanoparticles are mostly produced using glutaraldehyde for macro-chain cross-linking. We were the first to propose a method of obtaining BSA nanoparticles using natural components such as urea and L-cysteine [12,13]. In this case, urea plays the role of a chaotropic agent, which unfolds albumin chains and increases the availability for interaction with cysteine.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction had been previously reported in a study involving bovine hemoglobin microparticles [ 26 , 27 ]. In addition, Tazhbayev et al [ 28 ] demonstrated that a urea and cysteine mixture could also be used for cross-linking to affect the conformation change of bovine serum albumin.…”
Section: Resultsmentioning
confidence: 99%